Variation in Structure and Functional Diversity of Surface Bacterioplankton Communities in the Eastern East China Sea - Zuochun Wang; Pengfei Xie; Jun Dai; Lei Zhang; Qiao Yang; Xiaoling Zhang; Xi Yang (Journal of Marine Science and Engineering, 2023)
Bacterioplankton communities are critical components of varied ecosystems in the oceans. Their occurrences represent a variety of connections between environmental and ecological elements. However, our current knowledge about the shaping factors of surface bacterioplankton communities in the eastern East China Sea (ECS) is still limited. In this study, we reveal the spatial patterns of the taxonomic and functional profiles of the surface bacterioplankton communitiesies in the nearshore and offshore areas in the eastern ECS, based on 16S rRNA gene pyrosequencing and functional annotation analysis. The obtained results show that the surface bacterioplankton communities in the nearshore areas are mainly dominated by the firmicutes (85.9%), actinobacteria (8.1%), and proteobacteria (5.4%), which are mainly involved in organic compound metabolism. Meanwhile, different bacteria predominate the composition of the offshore group, namely proteobacteria (71.1%) and bacteroidetes (22.0%) responsible for nitrogen and sulfur metabolism. Furthermore, their distribution pattern is shown to be spatially determined, along with a modest finding of functional diversity when comparing the bacterial species. The primary two shaping factors of bacterioplankton diversity are found to be the offshore distance and temperature. Overall, these findings add to those previously published on bacterial species and offer up functional information on the surface bacterioplankton communities in the eastern ECS. To extend our research, we propose that, in the future, it may be beneficial to monitor the dynamics of the ecosystem in this sea area.